Assessment of Knowledge and Need for Further Education Related to Implant Dentistry in General Dental Practitioners of Palamu Area, Jharkhand - Tomar, Akhilesh; Kumari, Ayusha; H, Rajesh.; Shree, Reya; Kumari, Sonali; Sriwastva, Gourav (Journal of Neonatal Surgery, 2025)
Dental implant is a device that is installed into the jaw bone to retain prosthesis. There are no such surveys available regarding implant which is specifically conducted among general dental practitioners who are practicing in Palamu region of Jharkhand which is majorly a rural area. A cross sectional study was carried out among 71 general dental practionners of Palamu region of Jharkhand. A questionnaire set was framed with a total 23 questions. The results are made by gathering all the responses marked by the participating dentists and summarizing them in 3 same sections in which all the questions were framed. In the first section, the first 9 questions of the survey are based on basic knowledge of implant, in which on an average 55 out of 71 (77.47%) dentists had basic knowledge of implant. In the second section, 8 questions were based on clinical knowledge of implant, in which on an average 28 outof 71 (39.44%) had clinical knowledge of implant. In the third section, 6 questions are based on advances and implant education. On an average 33.80% of general dental practitioners have knowledge of basic surgical procedures like incision, type off lap, type of incision and about 81.70% of general dental practitioners don’t know about the advanced surgical procedures like sinus lift surgery, type of graft, GBR, GTR membrane. 80.28% of general dentists does not practice implant in their regular practice and about 84.51% finds implant placement to be difficult. The general dental practitioner should have adequate knowledge, skill and training which can be achieved by employing proper training and education to them.